Characteristics of Hypertension Patients in Coastal District Percut Sei Tuan - Zuhrina Aidha; Reni Agustina Harahap; Delfriana Ayu A (Universitas Teuku Umar, 2020)
Hypertension is a non-communicable disease that is a threat to people in developing countries. Hypertension is also called the silent killer which is the cause of death in Indonesia. The prevalence of hypertension in North Sumatra Province reaches 6.7% of the population in North Sumatra, based on data from the Ministry of Health's Health Research and Development Agency. This means that the population of North Sumatra suffering from hypertension reaches 12.42 million people spread across several districts (Ministry of Health, 2013). aro Regency is one of the highest numbers of hypertension, following Deli Serdang district. In 2016 the number of hypertensive patients in Karo Regency was 12,608 people, this prevalence was higher in female sex (52%) men (48%), the largest in the age group 55-59 years (Simbolon, 2016). This type of research is descriptive using the quantitative method with a cross sectional approach. Determination of the number of samples by simple random sampling, and obtained a sample of 30 people. Data analysis using univariate analysis to see the frequency distribution of each variable. The results of this study found that, 50% of respondents had high school education, 85% of respondents as housewives, respondents aged between 40-60 years, and 60% of respondents had a family history of hypertension.